2018
DOI: 10.1007/s11250-018-1628-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of energy density of diet on growth performance of Thai indigenous (50% crossbred) Korat chickens from hatch to 42 days of age

Abstract: The aim of the current study was to investigate the effect of the energy density of diet on the growth performance of Thai indigenous crossbred (50%) chickens known as Korat chicken (KRC). A total of 1440 mixed-sex KRC (720 birds in each phase) were randomly allocated to 4 dietary treatments containing 2750, 2900, 3050, or 3200 kcal ME/kg diet with 6 replicates of each treatment in a completely randomized design. The experimental diets were tested from hatch to 21 days and from 22 to 42 days of age. In both ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Similar to our previous study (El‐Senousey et al, 2019) and other studies (Maliwan et al, 2018; J. P. Wang et al, 2016), the BW, ADG and FCR increased significantly after increasing the dietary energy concentration. Xie et al (2010) also found that increasing the dietary energy concentration from 2451 to 3046 kcal/kg boosted the body weight gain while decreasing feed intake and enhancing the FCR in white Pekin ducks.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to our previous study (El‐Senousey et al, 2019) and other studies (Maliwan et al, 2018; J. P. Wang et al, 2016), the BW, ADG and FCR increased significantly after increasing the dietary energy concentration. Xie et al (2010) also found that increasing the dietary energy concentration from 2451 to 3046 kcal/kg boosted the body weight gain while decreasing feed intake and enhancing the FCR in white Pekin ducks.…”
Section: Discussionsupporting
confidence: 91%
“…One of the most important strategies for enhancing feed efficiency and reducing feed costs is to provide the optimal level of metabolizable energy (ME), which may enhance the economic efficiency of poultry production (Attia & Hassan, 2017; Attia et al, 2021; El‐Senousey et al, 2019; Maliwan et al, 2018). Nutrients have an impact on meat quality parameters (X. Q. Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The demand for food, particularly animal protein, in Indonesia, has been on the rise due to population growth, increased purchasing power, and a growing awareness of the importance of nutrition for a healthy lifestyle [1]. One strategy to enhance livestock potential and ensure food security is crossbreeding [18]. Currently, local Indonesian chicken breeds require further exploration to unlock untapped advantages, thereby obtaining high-quality breeding stock that can improve efficiency and production, providing more opportunities [2].…”
Section: Introductionmentioning
confidence: 99%